Bioinformatics and Network Pharmacology Identify the Therapeutic Role and Potential Mechanism of Melatonin in AD and Rosacea - Zhang, Huaxiong; Zhang, Yiya; Li, Yangfan; Wang, Yaling; Yan, Sha; Xu, San; Deng, Zhili; Yang, Xinling; Xie, Hongfu; Li, Ji (Frontiers in Immunology, 2021)
Rosacea is significantly associated with dementia, particularly Alzheimer's disease (AD). However, the common underlying molecular mechanism connecting these two diseases remains limited. This study aimed to reveal the common molecular regulatory networks and identify the potential therapeutic drugs of rosacea and AD. 747 overlapped DEGs (ol-DEGs) were detected in AD and rosacea, enriched in inflammation-, metabolism-, apoptosis-related pathways. Using the TF regulatory network analysis, 37 common TFs and target genes were identified as the hub genes. They were used to predict therapeutic drugs of rosacea and AD using DGIdb/CMap database. Among the 113 predicted drugs, melatonin (MLT) was co-associated both with RORA and IFN-γ in AD and rosacea. Subsequently, network pharmacology analysis identified 19 pharmacological targets of MLT and demonstrated that MLT could help in treating AD/rosacea partly by modulating inflammatory and vascular signaling pathways. Finally, we verified the therapeutic role and mechanism of MLT on rosacea in vivo and vitro. We found that MLT treatment significantly improved rosacea-like skin lesion by reducing keratinocyte-mediated inflammatory cytokines secretion and repressing the migration of HUVEC cells. In conclusion, this study contributes to common pathologies shared by rosacea and AD and identified MLT as an effective treatment strategy for rosacea and AD via regulating inflammation and angiogenesis.